Registration of 'S11‐20124C' Soybean with High Yield Potential, Multiple Nematode Resistance, and Salt Tolerance. Issue 2 (25th April 2019) - Shannon, G.; Nguyen, H. T.; Crisel, M.; Smothers, S.; Clubb, M.; Vieira, C. C.; Ali, M. L.; Selves, S.; Mitchum, M. G.; Scaboo, A.; Li, Z.; Bond, J.; et al.
Abstract : 'S11‐20124C' (Reg. No. CV‐532, PI 689118) is a high‐yielding semi‐determinate early maturity group V (5.1) conventional soybean [ Glycine max (L.) Merr.] cultivar developed and released in 2017 by the University of Missouri–Fisher Delta Research Center Soybean Breeding program. It was developed through conventional breeding from a cross between 'S05‐11482' × 'S06‐4649RR'. The development of high‐yielding conventional soybean became advantageous due to premium prices offered for non–genetically modified soybean products, as well as lower seed costs compared with herbicide‐tolerant cultivars. Additionally, early maturity group V (5.1) soybeans are highly desirable for early planting and after wheat ( Triticum aestivum L.) in double cropping systems. S11‐20124C was evaluated in 113 environments from 2012 to 2016 in Missouri and other southern states. It is demonstrated to be well adapted through its consistent superior or equivalent performance to the commercial checks with similar maturity. S11‐20124C has a wide disease resistance package, including moderate resistance to soybean cyst nematode races 1, 2, 3, 5, and 14 (HG Type 2.5.7, Type 1.2.5.7, Type 7, Type 2.5.7, Type 1.3.6.7 respectively) and resistance to southern root‐knot nematode and reniform nematode . Seed averages 416 g kg −1 protein and 245 g kg −1 oil. High yield potential, resistance to multiple diseases, and broad adaptation make S11‐20124C a good choice for soybean growers across US southern states.